2021
DOI: 10.1155/2021/7712587
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Disease-Modifying Antirheumatic Drugs and the Risk of Cardiovascular Events: A Systematic Review and Meta-Analysis

Abstract: Objective. To assess the association between the use of biological disease-modifying antirheumatic drugs (bDMARDs) and the risk of cardiovascular events in patients with systemic inflammatory conditions. Methods. Eligible cohort studies or randomized controlled trials (RCTs) from inception to January 2021 were included. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) for cardiovascular outcomes were calculated in the fixed- and random-effects model accordingly. Associated factors with risks of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…Although cardiovascular events were major concern among RA patients [28], only one case of cardiovascular event that led to treatment cessation was observed in our study. This may support previous ndings of reduced risks of cardiovascular events among b/tsDMARD users [29], though this may also due to short observational period of one year.…”
Section: Discussionsupporting
confidence: 90%
“…Although cardiovascular events were major concern among RA patients [28], only one case of cardiovascular event that led to treatment cessation was observed in our study. This may support previous ndings of reduced risks of cardiovascular events among b/tsDMARD users [29], though this may also due to short observational period of one year.…”
Section: Discussionsupporting
confidence: 90%
“…[ 11 ] However, a meta-analysis published recently indicated that the use of bDMARDs might be associated with the reduced risks of cardiovascular death in RA. [ 97 ] Different retrieval methods and calculation methods may lead to different results. More investigations are needed to validate conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Biologic disease-modifying therapies (bDMARDs) should be further investigated. Hu et al found a reduced risk of MI (OR 0.74, 95% CI 0.63-0.87), cardiovascular death (OR 0.62, 95% CI 0.40-0.95), and a composite endpoint of MI, stroke, and cardiovascular death (OR 0.69, 95% CI 0.53-0.89) in those on bDMARDs, compared with those not on bDMARDs [98]. These finding were mostly driven by the reduction of risk in rheumatoid arthritis patients, thus the role in SLE is unclear.…”
Section: Antiatherosclerotic Therapies In Slementioning
confidence: 99%